Non scripsit meus ista Martialis. Marcjalis o literackich paszkwilach - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
In this article the author discusses several epigrams of Martial VII, 12 and 72; X 3, 5 and 33, in which the poet complains about libels written under his name and circulated throughout Rome. The outrage of Martial is justified, because the poet almost intentionally avoided writing poems which would offend the reputation of any person.Defamatory epigrams circulated in Rome under his name, written by the poet’s competitors who envied his fame and recognition, were dangerous for him due to threats of accusation of defamation. The punishment of any behavior aimed at defaming another person, was introduced in Rome by edict ne quid infamandi causa fiat. It provided, inter alia, the possibility of a legal action for insult against any person who arranged the songs to defame another person with the intention to distribute them.As it seems, defamatory carmina were not punishable by law during the republic period. The situation changed during the principate period, when people reciting ridiculing poems at the feasts were met with repression. The works detrimental to the good name of the rulers resulted even in a charge of crimen maiestatis. Practising satirical works became a particularly risky occupation during the reign of Domitian, because the emperor declared a decisive fight against the authors of defamatory writings.Punishment by actio iniuriarum aestimatoria for the authors of libels, circulating in Rome as the works of Martial, however, was not easy. Firstly, the poet had to establish their authors, and secondly prove the intention of insulting him by the publication of such poems. A simpler form of defense was public denial of authorship of such epigrams. For this purpose, Martial called on his literary patrons, asking them to bear witness that he was not the author of this kind of libels.
Keywords: stan wojenny; zniesławienie w prawie rzymskim; epigram rzymski